Family adaptation as a predictor of family self-determination of digital generation students - S. V. Merzlyakova; E. P. Kayumova (Образование и наука)
Introduction. An accessible and contradictory Internet space creates threats and risks to traditional family values, contributes to the emergence of intergenerational problems, the formation of distortions in the marriage and family conception of young people in the context of digital socialisation. The relevance of the research problem associated with understanding the reasons for family self-determination is intensified by the fact that modern students are focused on career growth, status work, personal development, achievement of material prosperity, mobility, and the associated decrease in the importance of family and marriage institution, childbearing.Aim. The aim of the study is to detect the features of students’ family self-determination depending on the level of family adaptation (rigid, structured, flexible and chaotic) in the context of interaction of traditional and digital socialisation.Methodology and research methods. The theoretical and methodological basis of the study is the cultural-historical theory of cognitive development by L. S. Vygotsky; the ecological systems theory by U. Bronfenbrenner, supplemented by the techno-subsystem of G. Johnson, K. Puplampu; socio-cognitive concept of digital socialisation by G. U. Soldatova, A. E. Voiskounsky; “circumplex model” by D. H. Olson. The study involved 312 students aged between 17 and 25, born after 1995 and belonging to digital generation. To achieve the goal, the following methods were used: theoretical analysis, psychodiagnostic method and mathematical-statistical methods of data processing.Results. The present study demonstrated that the nature of the role structure of parental family (adaptation) is a meso-level factor, which determines the process of family self-determination of digital generation students. It has been established that the chaotic type of family adaptation prevails in parental families, in which students form the value of the parental family, the importance of mother and father, an emotionally positive attitude towards their own family and the ability to manage their lives. At the same time, there are also negative trends, which are manifested in the fact that students form excessive demands on a marriage partner in the household sphere, and the availability of an active life decreases. Students with a rigid level of adaptation differ from their peers in the lower significance of the role “As a son/daughter”, the values of marriage and family relations, life-meaning orientations, and self-doubt. Students with a structural level of family adaptation are characterised by a less positive attitude towards themselves and their father compared to other respondents. A flexible level of family adaptation is optimal and contributes to the development of the importance of filial or affiliated roles, purposefulness, meaningfulness of life, an emotionally positive attitude to the headship and responsibility in the family, self-confidence, internal locus of control.Scientific novelty of the research lies in the establishment of the connection between family adaptation and the content characteristics of students’ family self-determination under the conditions of interaction of traditional and digital socialisation.Practical significance. The applied aspect of the investigated problem of students’ family self-determination depending on the level of family adaptation can be implemented within the activities of psychological services of the university in providing assistance in the field of premarital and family counselling to resolve intergenerational problems, prevent the emergence of dysfunctional marriage in the future.